THE EFFECT OF DIAPHRAGMATIC BREATHING ON STRESS LEVELS OF NURSING STUDENTS AT PRIVATE UNIVERSITY IN TANGERANG - Saptono, Garuh Dwi; Kristiyani, Lavenia; Astuti, Wanda; Sinulingga, Elysabeth; Silaban, Winda (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2024)
Students were often stressed because of their exciting lecture and practical schedules, the difficulties of living in a dormitory, and other factors. Nursing students face various pressures in their personal lives and academic roles. Diaphragmatic breathing exercises are a form of therapy that can be used to reduce stress. Objective: The objective of the study was to find out how diaphragmatic breathing affected the stress level of nursing students at a private university in Tangerang, Banten. Methods: This study used a pre-experimental quantitative design with a one-group pretest and posttest research design. The method used is consecutive sampling, with a sample size of 225 respondents. This study used the Depression Anxiety Stress Scale (DASS-42) questionnaire administered between February and April 2024. Data analysis techniques include univariate and bivariate analyses using the Wilcoxon signed rank test. Results: The largest number of differences is at the normal level, which previously amounted to 104 people (46.2%) increased to 147 people (65.3%), meaning that there was an increase of 43 students (19.1%). While the least amount of difference is at a very severe level which only increased by 4 students (1.8%). The results of the bivariate analysis obtained a sig value (2-tailed) < 0.001 or equal to Sig < α 0.05, which means that there is a significant influence of diaphragmatic breathing exercises on students' stress levels. Discussion: The tight schedule of lectures and the pressure of dormitory life risk causing students to experience stress and can affect students in studying. One very simple and easy way to overcome stress is the diaphragmatic breathing technique. Conclusion: It is concluded that the provision of diaphragmatic breathing exercises has a significant effect on student stress levels. Keywords: diaphragmatic breathing, students, stress.